Perlindungan Hukum Terhadap Konsumen dalam Transaksi E-Commerce dalam Hal Wanprestasi - Haryono Haryono; Troeboes Soeprijanto; Lathifatu Khoirun Nisa (Persatuan Guru Republik Indonesia Kota Semarang, 2023)
Legal protection for consumers is a must provided by business actors to consumers, because this has been regulated in Law No. 8 of 1999 concerning Consumer Protection. The purpose of this study is to find out whether the legal protection for consumers in the event of default in Indonesia is in accordance with the value of justice and how is the legal protection for consumers in the event of default in E-Commerce transactions. The research method used is normative juridical, data collection is done through literature study. The results of the study are first that legal protection for consumers in the event of default in an E-Commerce transaction, namely that the consumer gains achievement and the consumer is entitled to compensation. When a business actor provides compensation or compensation for default or negligence, this is a form of legal protection for the consumer, because the promised performance has been fulfilled by the business actor in accordance with the agreement. Second, consumer protection in the event of default in E-Commerce transactions in Indonesia is in accordance with the value of justice. The implementation of this principle of justice is stated in Article 4 to Article 7 of Law No. 8 of 1999 concerning Consumer Protection which regulates the rights and obligations of consumers and business actors. Through this principle, consumers and business actors are expected to get their rights and fulfill their obligations in a balanced way.